ESR dating of Pleistocene mammals and marine shells from the coastal plain of Rio Grande do Sul state, southern Brazil - Lopes, Renato P.; Kinoshita, Angela; Baffa, Oswaldo; Figueiredo, Ana Maria Graciano; Dillenburg, Sérgio Rebello; Schultz, Cesar Leandro; Pereira, Jamil Corrêa (Quaternary international, 2014)
The Coastal Plain of Rio Grande do Sul state (CPRS), in southern Brazil, encompasses four barrier-lagoon depositional systems formed by marine highstands during the Quaternary, but the ages of the Pleistocene systems older than ∼125 ka are not precisely known due to the lack of numerical dates. In order to refine the chronology of these deposits, several fossils of terrestrial mammals collected in the fluvial facies of the Lagoon System III and fossil shells from the marine facies of the Barrier System II, exposed in the southern sector of the CPRS, were subject to dating by electron spin resonance (ESR). The ages of the mammalian remains range from 90 ± 10 to 43 ± 3 ka, thus representing the last glacial cycle (MIS 4 and 3). The mean EU age of the shells is 224 ± 24.6 ka, but this value is considered younger than the ‘real’ age because of excessive Uranium uptake observed among the younger shells. An estimated mean age of some 235–238 ka would agree with other ESR and TL ages obtained for fossils and sediments collected from beds overlying the shells, and would be consistent with the sea-level highstand at the early MIS 7 (substage 7e). The presence of bivalves and foraminifers that indicate ocean temperatures higher than at present seems to corroborate this estimate, given that MIS 7e was characterized by hypsithermal conditions.